Immediate "Kangaroo Mother Care" and Survival of Infants With Low Birth Weight. Issue 4 (22nd December 2021) - Arya, S.; Naburi, H.; Kawaza, K.; Newton, S.; Anyabolu, C.H.; Bergman, N.; Rao, S.P.N.; Mittal, P.; Assenga, E.; Gadama, L.; Larsen-Reindorf, R.; Kuti, O.; et al.
Abstract : ( N Engl J Med . 2021;384:2028–2038. doi: 10.1056/NEJMoa2026486. PMID: 34038632; PMCID: PMC810848) While preterm, low–birth-weight infants make up ~15% of neonates, they account for the vast majority of neonatal deaths (70%). "Kangaroo Mother Care, " where the mother or caregiver provides continuous skin-to-skin contact with the neonate, has been shown to decrease mortality in infants with a birth weight below 2.0 kg. This study aimed to determine when to initiate continuous kangaroo mother care and if it is safe.